2014
DOI: 10.1007/s11205-014-0737-0
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and Athletes’ Life Satisfaction: A Intra-individual Analysis on the Moderation of Ambivalence over Emotional Expression

Abstract: Original citation:Chen, Lung Hung, Wu, Chia-Huei and Chen, Shouming (2015) Gratitude and athletes' life satisfaction: a intra-individual analysis on the moderation of ambivalence over emotional expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…In general, gratitude conceptualized as both disposition and state or emotion. Gratitude is eternal gratitude that continues throughout the situation and over time (Chen, Wu, & Chen, 2015). Initially, gratitude defined as the general tendency to recognize and respond emotionally to the virtue the others and positive results obtained by someone.…”
Section: Gratitude and Happinessmentioning
confidence: 99%
“…In general, gratitude conceptualized as both disposition and state or emotion. Gratitude is eternal gratitude that continues throughout the situation and over time (Chen, Wu, & Chen, 2015). Initially, gratitude defined as the general tendency to recognize and respond emotionally to the virtue the others and positive results obtained by someone.…”
Section: Gratitude and Happinessmentioning
confidence: 99%
“…Gratitude, on the other hand, is the process of bringing more of what you want into your life; if you are grateful you will be given more, and you will have an abundance (Byrne, 2012). Innumerable studies about gratitude have already been conducted in other countries and these studies have found the relationship between gratitude and happiness (Froh et al, 2008;Sheldon & Lyubomirsky, 2006;Walker & Pitts, 1998(as cited in Emmons & McCullough, 2003; Overwalle et al, 1995(as cited in Emmons & McCullough, 2003; McCullough et al, 2001;Emmons & McCullough, 2003;Nelson & Lyubomirsky, in press;Elosua, 2015;Chen et al, 2015;Adler & Fagley, 2005;Watkins et al, 2008;Chan 2010;Wood et al, 2009;Emmons & Crumpler, 2000;Emmons & Shelton, 2002;Wood et al, 2010;Chan, 2013a;Chan, 2013b;and Marti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%